L’humour fellaguien comme lieu d’inventivité lexicale francophone - Zollo, Silvia Domenica (Ponti/Ponts, 2024)
In this contribution, we analyse the lexical inventiveness of Mohamed Saïd Fellag, a Kabyle-speaking Algerian comedian and humorist, with the aim of describing the processes of morpho-lexical creation and characterising the contexts in which these new words appear. In a logic of testimony and experiential narrative, both individual and collective, he creates a ‘théâtre-constat’ in which humoristic and playful neology plays a cathartic role. We will first present the author, the corpus compiled ad hoc and the theoretical and methodological framework adopted for its treatment. We will then attempt to explain the reasons that motivate, in our opinion, the flowering of Fellaguian neologisms, paying particular attention to the processes of morpho-lexical production and their functions in discourse.